O uso de um novo diluidor para congelamento de sêmen de jumento na inseminação de fêmeas equinas com ovulação induzida - Flavia Pereira Costa (2015)
This study was carried out in Lagoa Dourada county, Minas Gerais State, from December 2013 to March 2014, with the aim of propose, produce and utilize a new extender for freezing donkey semen, as part of a new protocol. Also, the pregnant rates of mares inseminated after detection of ovulation, induced by hCG, were evaluated. Those animals were submitted to a follicular control at every 8-hour interval after drug administration, when a follicle higher than 30-35mm diameter and uterine edema 2 were recorded. Two Pêga breed donkeys were used as semen donors. After collection, semen was frozen using two extenders: (1) glucose-skimmed milk powder (GSMP) egg yolk ethylene glycol (Jepsen, 2010) and (2) PIVO-2013. Mares were inseminated post-ovulation with frozen-thawed semen, from both extenders with an insemination dose of 5mL (300.00 x 106 338.89 ± 7,35 x 106 mobile spermatozoa / insemination dose), with deposition of semen inside the uterus body. The pregnant rates were 23.81% (5/21) and 55.56% (10/18), respectively, for extenders 1 and 2 (p<0,05), respectively. Seminal characteristics differed between donkeys, showing individual variation. The pregnant rates per donkey were 28.57% (6/21) and 50% (9/18), respectively, for donkeys 1 and 2. The administration of 1,666 IU of hCG was efficient to induce ovulation, being the majority of the ovulations observed within 30 to 40h after induction